Factors analysis affecting nurse efficacy in implementing resuscitation in cardiac arrest patients - Ahsan, Ahsan; Tualeka, Abdul Rohim; Rahmawati, Pudji; Russeng, Syamsiar S.; Susilowati, Indri H.; Jalaludin, Juliaa (Universidad del Zulia, 2020)
Research on self-efficacy against resuscitation cases in patients with heart disease are still small, especially in Indonesia. The aim of this research is to measure type of research is Self-efficacy using The General Self-efficacy Score. The majority of respondents are males(66.7%),with a mean age of 32.93 and a majority of education is the D-III Nursing (80%).There is a correlation between Mastery experience and verbal persuasion with self-efficacy nurses with mastery experience as the dominant factor in carrying out resuscitation in patients with cardiac arrest in the emergency room at the General Hospital Dr. R. Koesma Tuban.